Telomere maintenance in African trypanosomes - Li, Bibo (Frontiers in Molecular Biosciences, 2023)
Telomere maintenance is essential for genome integrity and chromosome stability in eukaryotic cells harboring linear chromosomes, as telomere forms a specialized structure to mask the natural chromosome ends from DNA damage repair machineries and to prevent nucleolytic degradation of the telomere. In Trypanosoma brucei and several other microbial pathogens, virulence genes involved in antigenic variation, a key pathogenesis mechanism essential for host immune evasion and long-term infections, are located at subtelomeres, and expression and switching of these major surface antigens are regulated by telomere proteins and the telomere structure. Therefore, understanding telomere maintenance mechanisms and how these pathogens achieve a balance between stability and plasticity at telomere/subtelomere will help develop better means to eradicate human diseases caused by these pathogens. Telomere replication faces several challenges, and the “end replication problem” is a key obstacle that can cause progressive telomere shortening in proliferating cells. To overcome this challenge, most eukaryotes use telomerase to extend the G-rich telomere strand. In addition, a number of telomere proteins use sophisticated mechanisms to coordinate the telomerase-mediated de novo telomere G-strand synthesis and the telomere C-strand fill-in, which has been extensively studied in mammalian cells. However, we recently discovered that trypanosomes lack many telomere proteins identified in its mammalian host that are critical for telomere end processing. Rather, T. brucei uses a unique DNA polymerase, PolIE that belongs to the DNA polymerase A family (E. coli DNA PolI family), to coordinate the telomere G- and C-strand syntheses. In this review, I will first briefly summarize current understanding of telomere end processing in mammals. Subsequently, I will describe PolIE-mediated coordination of telomere G- and C-strand synthesis in T. brucei and implication of this recent discovery.